The Concept of Alienation and Alienation in Organizations - Ghaleb, Belal Dahiam Saif (Pancasila International Journal of Applied Social Science, 2024)
Although the concept of alienation has been studied in the literature for years, it is a topic that has not lost its currency. This article delves into the enduring significance of the concept of alienation, examining its historical development, causes, and consequences within the context of organizational settings. Alienation, characterized by an individual's loss of faith in their environment and self, manifests as a disorder leading to profound loneliness and hopelessness. The study particularly focuses on workplace alienation, highlighting the inherent conflict between job demands and an employee's intrinsic nature. Organizational alienation is explored as a nuanced reflection of an individual's emotions arising from dissatisfaction within the employment context. The research conducts a thorough analysis of individual, social, and sociological consequences, unraveling the far-reaching impact of alienation on both personal and organizational levels. In response to the challenges posed by alienation in organizations, strategic interventions are proposed to mitigate its pervasive effects and cultivate a positive and cohesive organizational environment. This comprehensive exploration amalgamates insights from existing literature, providing a professional and detailed examination of the complex phenomenon of alienation. in this article, the influence of culture (Cultural Norms and Values, Communication Style, Inclusiveness and Diversity, Leadership Style, Organizational Structure, Workplace Rituals and Traditions, and Employee Recognition and Pay Systems) on organizational alienation and the importance of culture in this context are emphasized. The article contributes valuable information to deepen the understanding of alienation's implications for individuals and organizations, offering insights for developing strategies to address and prevent alienation in organizational contexts.